Factors that affect the English language teaching-learning process in Ecuadorian public high schools - Jaramillo Guamán, Diego Armando (2013)
The topic of this study is “Factors that affect the English language teaching-learning process in Ecuadorian public high schools”. The general objective of this research was to analyze the factors that affect the English language teaching-learning process. To do this research study, it was necessary to analyze four important factors, factors concerning teachers, students, classroom, and educational institution. This research was conducted in five public high schools from the urban area in Machala city. These high schools were chosen randomly. The population for this study comprised fifteen teachers from different grades and fifteen students chosen randomly. The instruments to collect the information were teacher’s questionnaires, students’ questionnaires, teachers’ interviews and observation of classes. The analysis of this information was made quantitatively. The main conclusion reached is that the factor that most affect the teaching learning process is the factor concerning teachers. Many teachers do not use English most of the time in their classes. So, the students do not have the opportunity to interact with their teachers in English, and it can affect the teaching and learning process